Emotional development in postgraduate students through the application of machine learning - Moreira-Choez, Jenniffer Sobeida; Villota-Oyarvide, Wellington Remigio; Meza-Arguello, Danny Meliton; Valdés-Cabodevilla, Regla Cristina; Loor-Rivadeneira, Marlene Ruth Elena; Mendoza-Fernández, Verónica Monserrate; Lapo-Palacios, Miguel Ángel; Sabando-García, Angel Ramón (Frontiers in Education, 2025)
IntroductionEmotional development is a central component in the academic formation and well-being of students, particularly at the postgraduate level, where academic, professional, and personal demands are considerable. This study aimed to analyze the emotional development of postgraduate students at the State University of Milagro through the application of machine learning.MethodologyThe approach was quantitative, with a non-experimental and cross-sectional design. The TMMS-24 scale was employed to measure perceived emotional intelligence across dimensions such as attention, clarity, and emotional regulation. The sample, composed of 1,412 participants, was analyzed using various machine learning models, including AdaBoost, Random Forest, SVM, logistic regression, and KNN, evaluated through metrics such as AUC, accuracy, and recall.ResultsAdaBoost and Random Forest were the most effective models, with AUC values of 0.996 and 0.972, respectively. AdaBoost achieved the highest F1-score (0.974), while Random Forest reached perfect recall (1.000) in students over 30. Both models showed strong predictive capacity across age groups. In contrast, logistic regression and SVM displayed limited performance, with AUCs below 0.56. These results confirm the superiority of ensemble methods in modeling emotional patterns.ConclusionIt is concluded that ensemble algorithms such as AdaBoost and Random Forest are effective tools for analyzing emotions in educational contexts. However, the study’s scope was restricted to an academic setting. As a practical implication, the findings support the integration of emotionally focused interventions in higher education programs to enhance students’ emotional development according to their specific needs.